Addendum: Aisami and Gusmanizar. Characterization of an Acrylamide-degrading Bacterium Isolated from Hydrocarbon Sludge. Bioremediation Science and Technology Research, 2019, Vol 7, No 2, 15-19. (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2020)
One of the authors has been unintentionally left out and the list of authors and affiliation should be added as follows.Abubakar Aisami 1* Neni Gusmanizar2 and Mohd Yunus Shukor31Department of Biochemistry, Gombe State University, P.M.B. 127, Tudun Wada,Gombe, Gombe State, Nigeria.2Department of Animal Nutrition, Faculty of Animal Science, Andalas University,Padang, 25163, Indonesia.Department of Biochemistry, Faculty of Biotechnology and Biomolecular Sciences, Universiti Putra Malaysia, 43400 UPM Serdang, Selangor, Malaysia. *Corresponding author addressDr Abubakar AisamiDepartment of Biochemistry,Gombe State University,P.M.B. 127, Tudun Wada,Gombe, Gombe State,Nigeria.Emel: abubakar.aisami05@gmail.com The Acknowledgement section (p.19) has been left out, and it should be added as follows. Acknowledgment We acknowledge the help of Mr Kesavan in isolating the bacterium and the late Dr Neni Gusmanizar (author) who helped to identify the bacterium, of which this manuscript is dedicated to her.